Food as Medicine: A Review of Plant Secondary Metabolites from Pollen, Nectar, and Resin with Health Benefits for Bees - Bandele Morrison; Laura R. Newburn; Gordon Fitch (Insects)
Bees rely on pollen and nectar for nutrition, but floral products provide more than just macronutrients; many also contain an array of plant secondary metabolites (PSMs). These compounds are generally thought to serve primarily defensive purposes but also appear to promote longevity and immune function, protect against disease agents, and detoxify toxicants. This review presents a comprehensive overview of PSMs, as well as some fatty acids, with documented health benefits for eusocial bees at ecologically relevant exposure levels and the plant species whose floral products and/or resin are known to contain them. We find medicinal metabolites to be widespread but unevenly distributed across the plant phylogeny, with a few families containing a majority of the species known to produce PSMs with documented health benefits. We discuss the current state of knowledge and identify gaps in our understanding. The existing literature on the health benefits of metabolites, and particularly PSMs, to bees is spread across multiple fields; our hope is that this review will bring these fields closer together and encourage further investigation of the role of metabolites in promoting bee health in ecological contexts.